The Link between Chronic Pain and Depression in Low Income Country, Pakistan - Mamoona Bokhari; Saima Dawood (Journal of the Pakistan Medical Association, 2021)
Objective: To examine the relationships of chronic pain related variables (interference, support, pain severity, life control, affective distress, significant other’s responses to participant’s pain and general activity level) with depression in chronic pain patients. Method: Cross-sectional survey research was used in this study. The study was carried out on outdoor patients coming in government, semi-government and private hospitals of Lahore city (n=6) from January 2016 to June 2016. Sample consisted of 186 chronic pain patients (mean age=46.92) with organic, identifiable chronic pain problems were recruited through purposive sampling. A personal history questionnaire, West Haven-Yale Multidimensional Pain Inventory (WHYMPI) developed by Kerns, Turk, and Rudy (1985), and Depression subscale of Symptom Checklist Revised developed by Rahman and Sitwat (1990) were administered to the participants. Results: Descriptive analyses, Pearson product moment correlation coefficient, independent samples t-test and stepwise regression with backward elimination method were used to analyze the data. It was revealed that all chronic pain related variables had significant relationships with depressive symptoms. Moreover, interference, affective distress and negative responses were found to be positive predictors while life-control was the negative predictor of depressive symptoms. It was also found that women reported more depressive symptoms than men. Conclusion: The study affirmed the relationships between chronic pain related variables and depressive symptoms and also highlighted the importance of significant other’s support and response to participant pain. The results thus emphasized the significance of familial factors with regard to the presence of depressive symptoms in chronic pain patients. Continuous...